The Financial Future of Global Football: A Systematic Review - Asghari, Zahra; Vali Nejad, Bahman; Naderi Nasab , Mehdi; Allahyari, Hossein (Journal of Foresight and Health Governance, 2025)
This study systematically reviews peer-reviewed evidence (2020–2026, plus key conceptual frameworks) to identify high-confidence trends and plausible scenarios for global football finance through 2030, focusing on (i) regulated financial governance, (ii) structural cost inflation and soft budget constraints, (iii) competitive balance and market stratification, (iv) women’s football commercialization and sustainability, and (v) transfer-market scaling and volatility. Because the evidence base is methodologically heterogeneous—spanning meta-analysis, panel econometrics, league-level concentration studies, club financial accounts analysis, and transfer-market modeling a single pooled-effect meta-analysis was not feasible. Instead, we integrated meta-analytic evidence on UEFA financial regulation outcomes with convergent results from large-sample econometric and multi-league studies. Across domains, five consistent signals emerge. First, revenue resilience depends heavily on diversification; clubs with broader revenue mixes appear less exposed to shocks. Second, cost inflation remains structurally embedded, as competitive incentives channel incremental revenues into wages and transfers, consistent with soft budget constraint dynamics. Third, financial regulation (notably UEFA’s FFP) is more reliably associated with improvements in profitability-related outcomes than with deep sustainability measures such as solvency. Fourth, competitive balance risks may increase in several contexts after regulation, suggesting stratification effects when rules interact with pre-existing inequality. Fifth, women’s football and transfers are major growth frontiers but carry sustainability risk: women’s clubs may sustain losses and rising debt despite revenue momentum, while transfer markets exhibit systematic pricing determinants yet remain vulnerable to volatility under shocks and tightening constraints. Overall, the evidence supports a “regulated growth under inflationary cost pressure” outlook for football finance through 2030, emphasizing the need for governance designs that address both financial discipline and distributional competitive effects.